2006
DOI: 10.2337/diacare.29.03.06.dc05-1703
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Body Weight in Type 2 Diabetes

Abstract: OBJECTIVE -There is a concern that an "epidemic of obesity" is occurring in Western societies. One consequence of obesity is that type 2 diabetes may develop. Presumably, a great increase in body weight would continue in people with diabetes and may be accelerated due to pharmacological treatment. In this retrospective study, we tested the hypothesis that the weight gain in a diabetic population is greater than that in the general population.RESEARCH DESIGN AND METHODS -Data were obtained from the records of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 16 publications
(14 reference statements)
2
37
0
2
Order By: Relevance
“…In addition, we found that higher proportion of insulin users in this group than in other weight trajectory groups, supporting previous research linking insulin use and weight accumulation. 3,20 Since obesity and weight gain are risk factors for diabetes prognosis, more focus should be placed on constructing coping strategies to counteract insulin-related weight gain, especially in obese adults with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we found that higher proportion of insulin users in this group than in other weight trajectory groups, supporting previous research linking insulin use and weight accumulation. 3,20 Since obesity and weight gain are risk factors for diabetes prognosis, more focus should be placed on constructing coping strategies to counteract insulin-related weight gain, especially in obese adults with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Research in clinical and community settings has examined general weight change patterns in adults living with diabetes over time, yielding inconsistent findings [2][3][4][5][6][7] and suggesting that the longitudinal course of body weight in middle-aged and older adults with diabetes exhibits not only intra-individual but also inter-individual variation.…”
mentioning
confidence: 99%
“…This suggests that, for Japanese T2DM patients, the addition of either biguanide or TZD to sulfonylurea does not necessarily improve glycemic control. It has been reported that the metformin monotherapy reduced body weight and reversed the weight gain by sulfonylurea in combination with sulfonylurea, while BMI of the patients treated with sulfonylurea alone compared with sulfonylurea plus metformin was variable [26,27]. Our study was not longitudinal and could not detect the changes in body weight, therefore, we could not discuss the desirable effect of metformin on BMI.…”
Section: Acknowledgementsmentioning
confidence: 59%
“…I n a recent volume in this journal, Chaudhry et al (1) reported their findings of weight change in 205 men with diabetes. They conclude that over the course of at least 5 years, modest weight gain is the norm in men with diabetes.…”
mentioning
confidence: 99%